The Seepage-Destruction Mechanism of Water Inrush Channel of Sandstone Fault Filling Using the EDEM-Fluent Method - Wenya Cai; Yan Wang; Fujun He; Pengyuan Zhang; Shuo Sun (Advances in Civil Engineering)
By the EDEM-Fluent coupling calculation method, the formation mechanism of the seepage failure water inrush channel and the migration of particles in the sandstone fault filling body are studied. Under the condition of variable hydraulic gradient, the whole seepage process can be divided into three stages: slow seepage stage, sudden seepage stage, and stable seepage stage. In the stage of slow seepage, the mass of lost particles is small. In the stage of sudden seepage, particles are lost on a large scale. In the stable seepage stage, the model is basically in a stable state. During the seepage process, the particles in the outlet zone will move before the particles in the inlet zone under the action of the seepage force. The overall movement trend of particles can be predicted, while the movement trajectory of a single particle is irregular. The change trend of the contact quantity between particles is basically consistent with the change in the quality of the lost particles. Moreover, the change in the contact quantity of particles is caused by the loss of the filler particles.